Banana Plant as Ruminant Feed - Wina, Elizabeth (Indonesian Animal Sciences Society, 2001)
Banana plant is a very common and very quickly multiplied plant in tropical areas such Indonesia. Its potential usage as animal or ruminant feed in Indonesia has not been deeply studied, whereas in Latin American countries, this plant has been well used as animal feed. The proximate analysis shows that the moisture content is extremely high in pseudostem, which can be a hindrance in intake. The ash content is also very high indicating a very high mineral level in pseudostem. The water fraction, contained high soluble minerals, phenolic compounds and simple sugar compounds, whereas the presence of starch in corm may be used as an energy source. Feeding banana plant usually is mixed with other feedstuff as protein or energy source, therefore banana plant is utilized as roughage substituting grasses. There is a need to look for other potential usage of banana plant, which may be as energy or mineral source or as protein protector. Â Key words: Banana, ruminant